2018
DOI: 10.1016/j.nicl.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Differences in atypical resting-state effective connectivity distinguish autism from schizophrenia

Abstract: Autism and schizophrenia share overlapping genetic etiology, common changes in brain structure and common cognitive deficits. A number of studies using resting state fMRI have shown that machine learning algorithms can distinguish between healthy controls and individuals diagnosed with either autism spectrum disorder or schizophrenia. However, it has not yet been determined whether machine learning algorithms can be used to distinguish between the two disorders. Using a linear support vector machine, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 70 publications
7
45
0
1
Order By: Relevance
“…As noticed empirically that the NBS was producing about 300 connection using a p-value threshold related to the t-test of α = 0.05 (proportionally in agreement with Mastrovito et al [16]), we lowered the NBS threshold to α = 0.01 to allow visual inspection of those results.…”
Section: Functional Connectivity Differencessupporting
confidence: 70%
See 1 more Smart Citation
“…As noticed empirically that the NBS was producing about 300 connection using a p-value threshold related to the t-test of α = 0.05 (proportionally in agreement with Mastrovito et al [16]), we lowered the NBS threshold to α = 0.01 to allow visual inspection of those results.…”
Section: Functional Connectivity Differencessupporting
confidence: 70%
“…Recently, Yahata et al identified a small number of connections which can discriminate ASD subjects from healthy control [15]. Mastrovito et al compared atypical functional connectivity between ASD to typically developing children and schizophrenia to normal control, highlighting also common connectivity features between ASD and schizophrenia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sparse models follow a feature selection agenda to subselect among existing variables, whereas PCA dimensionality reduction follows a feature engineering agenda to generate a set of new variables. A feature selection by sparse model is indeed similar to the RFE used by Mastrovito et al 19 . However, the stability of RFE approach depends heavily on the type of model used for feature ranking at each iteration, and as shown empirically, using regularized ridge regression jointly to stability selection criteria can provide more stable results in terms of stability selection of features, and yields finite sample familywise error control 28,29 .…”
Section: Relation To Previous Methodsmentioning
confidence: 93%
“…While, Chen et al 18 enhanced NBS regulating the topological structures comprised. Other research groups [19][20][21] leveraged support vector machines (SVM) weights to identify discriminating regions. SVM is a supervised learning method which constructs a hyperplane or set of hyperplanes in a high-or infinite-dimensional space used for classification.…”
Section: Local Differences Between Connectomesmentioning
confidence: 99%
See 1 more Smart Citation